Editorial: Social, technological and health innovation: Opportunities and limitations for social policy, health policy, and environmental policy - Andrzej Klimczuk; Magdalena Klimczuk-Kochańska; Jorge Felix (Frontiers in Political Science, 2022)
Innovation is progressively needed in responding to global challenges. Moreover, the increasing complexity of challenges implies demand for the usage of multisectoral and policy mix approaches. Wicked problems can be tackled by "integrated innovation" that combines the coordinated implementation of social, technological, and health innovation co-created by entities of the public sector, the private sector, the non-governmental sector, and the informal sector. This Research Topic focuses on filling the knowledge gaps about the selected types of innovation. First, regarding social innovation that can be understood as new strategies, concepts, products, services, and organizational forms that allow the satisfaction of human needs. Second, a technological innovation that refers to new or remarkably improved products, goods, or services in terms of their technical specifications, components, materials, software, design, or other functional features. Third, health innovation that focuses on novel or enhanced health policies, systems, products, technologies, services, and care delivery schemes to improve people's health. Finally, this Research Topic highlights attempts to develop integrated innovation that can add value to social policy, health policy, and environmental policy by improving efficiency, effectiveness, quality, sustainability, safety, and affordability.
Keywords: F64; H53; H75; I18; O13; O31; O35; O36; O38; Q55; Z18; 330; digital health; health innovation; integrated innovation; multisectoral policy; public policy; public health; social innovation; technological innovation